The Reef Fish Community Structure in Penyusuk Waters, Bangka Regency, Indonesia (Case Study of Artificial Reef in PT. Artha Cipta Langgeng) - Hafizah, Adisti; Adibrata, Sudirman; Muftiadi, M. Rizza; Balisco, Rodulf Anthony T. (Yayasan Serumpun Karang Konservasi, 2023)
Reef fishes are important components of a healthy coral ecosystem. However, when coral reefs are degraded, reef fishes also lose their habitat resulting in a decline in reef fish production and sustainable livelihood for the communities depending on it. In this study, we determined the status of reef fish communities in an artificial reef at PT Artha Cipta Langgeng in the Penyusuk waters of Bangka Regency, Indonesia. Data on reef fish communities were collected using the underwater visual census (UVC) method, including in situ and ex-situ environmental parameters. A total of 2,987 individuals belonging to 12 reef fish species and five families were recorded across three stations. The abundance of reef fish ranges from 45 to 60 ind/m², categorized as highly abundant. Diversity, evenness, and dominance indices were calculated at 1.18-1.49, 0.56-0.65, and 0.26 -0.36, respectively which are categorized as low to moderate. The environmental parameters in the artificial reef are still within the standard limit for a reef ecosystem. The study emphasizes the importance of artificial reefs as an alternative to a degraded coral reef ecosystem in supporting the thriving existence of reef fishes in the Penyusuk waters.